PERLINDUNGAN KONSTITUSIONAL HAK MASYARAKAT HUKUM ADAT ATAS TANAH - Lalu Sabardi (Jurnal Cakrawala Hukum, 2017)
This research aimed to develop the legal protection thinking to the custom (adat) community rights as the partof the human rights protection.The implication of it was then seen toward human rights protection of custom(adat)-law community in land matters field. This was a normative research. As the normative research, it usedprimary, secondary, and tertiary legal materials. The result was the recognition of state on the application ofhuman rights to the right of community on the land with the conditional recognition pattern. As a result, itsimplication extremely depended on the governmental legal politic.